Hide and seek: Plasticity of innate lymphoid cells in cancer. (February 2019) - Bald, Tobias; Wagner, Marek; Gao, Yulong; Koyasu, Shigeo; Smyth, Mark J.
Abstract: The advance of immunotherapies has revolutionized the treatment of cancer patients. Mostly agents modulating the adaptive immune system are currently used. More recently, attempts to stimulate the innate immune system are being promoted for clinical evaluation. Innate lymphoid cells (ILCs) are a highly plastic population of immune cells crucial for tissue homeostasis and the regulation of immune responses and maybe a promising target to improve current cancer immunotherapies. Although we have made significant progress in understanding ILC biology, their impact on tumor development, progression and therapy is controversial. In this review, we discuss the recent advances of ILC function and plasticity in the context of cancer.